Kicking, Throwing, Grappling: How Combat Sports Shape Muscular Fitness and Motor Competence in Children - Stevan Stamenković; Hrvoje Karničić; Jadranka Vlašić; Anja Topolovec; Damir Pekas (Journal of Functional Morphology and Kinesiology)
Background/Objectives: This study aimed to examine differences in motor competence and muscular fitness between children engaged in combat sports and their peers who do not participate in structured physical activity. Methods: The sample consisted of 120 healthy eight-year-old children, evenly divided into two groups: 60 children practicing combat sports (karate, judo, and wrestling) for at least one year and 60 children without structured sports involvement. Motor competence was assessed using the Test of Gross Motor Development-2 (TGMD-2), while muscular fitness was evaluated through standing broad jump, grip strength, 30 s sit-ups, bent arm hang, medicine ball throw, and push-ups. For differences between groups, the independent samples t-test was performed. Results: Results indicated that children practicing combat sports demonstrated significantly higher locomotor and manipulative skills (p < 0.01, ES = 0.76–1.25) and superior muscular fitness across all tests (p < 0.01, ES = 0.53–1.09) compared to their peers. Conclusions: These findings highlight the positive impact of combat sports on overall physical development, particularly in enhancing motor competence, muscle strength, and endurance. Given the critical role of motor competence and physical fitness at this age, integrating combat sports into daily routines can support long-term athletic development, encourage physical activity, and enhance overall health. Future research should explore the influence of specific combat sports on distinct physical attributes and consider additional factors such as total physical activity levels.